Antimicrobial resistance in large clostridial toxin-negative, binary toxin-positive Clostridium difficile ribotypes. (December 2018) - Androga, Grace O.; Knight, Daniel R.; Lim, Su-Chen; Foster, Niki F.; Riley, Thomas V.
Abstract: Antimicrobial resistance (AMR) is commonly found in Clostridium difficile strains and plays a major role in strain evolution. We have previously reported the isolation of large clostridial toxin-negative, binary toxin-producing (A − B - CDT + ) C. difficile strains from colonised (and in some instances diarrhoeic) food animals, as well as from patients with diarrhoea. To further characterise these strains, we investigated the phenotypic and genotypic AMR profiles of a diverse collection of A − B - CDT + C. difficile strains. The in vitro activities of 10 antimicrobial agents were determined for 148 A − B - CDT + C. difficile strains using an agar dilution methodology. Whole-genome sequencing and in silico genotyping was performed on 53 isolates to identify AMR genes. All strains were susceptible to vancomycin, metronidazole and fidaxomicin, antimicrobials currently considered first-line treatments for C. difficile infection (CDI). Differences in antimicrobial phenotypes between PCR ribotypes (RTs) were observed but were minimal. Phenotypic resistance was observed in 13 isolates to tetracycline (TetR, MIC = 16 mg/L), moxifloxacin (MxfR, MIC = 16 mg/L), erythromycin (EryR, MIC ≥128 mg/L) and clindamycin (CliR, MIC = 8 mg/L). The MxfR strain (RT033) possessed mutations in gyrA/B, while the TetR (RT033) strain contained a tetM gene carried on the conjugative transposon Tn 6190. All EryR and CliR strains (RT033, QX521) were negative for the erythromycin ribosomal methylase gene ermB, suggesting a possible alternative mechanism of resistance. This work describes the presence of multiple AMR genes in A − B - CDT + C. difficile strains and provides the first comprehensive analysis of the AMR repertoire in these lineages isolated from human, animal, food and environmental sources. Highlights: Antimicrobial resistance (AMR) is common in C. difficile . Susceptibility testing generally focuses on toxigenic C. difficile strains. CDI due to non-toxigenic CDT producing strains (A - B - CDT + ) is under-reported. AMR genes were identified in A - B - CDT + C. difficile strains from various sources. These findings emphasize the importance of a One Health approach in combating AMR.